GROWTH FALTERING AND INADEQUATE DIETARY INTAKE AMONG CHILDREN (6-23 MONTHS OLD) IN SISSALA EAST DISTRICT, GHANA - Suara, S. B.; Aryee, P. A. (UDS International Journal of Development, 2018)
Inappropriate complementary feeding and anthropometric deficits in children within 6-23 months old is a major problem in Sissala East District. The objectives of this study were to assess the proportions of children who received complementary foods below World Health Organization’s (WHO) recommended infant feeding practices and prevalence of anthropometric deficits. A total of 354 child-mother pair was randomly recruited for the study. Data were collected on child dietary intake and demographic variables of mother-child pair between February and March, 2013. Child nutritional status was assessed based on anthropometric measurements. Prevalence of minimum diet diversity (MDD), minimum meal frequency (MMF) and minimum acceptable diet (MAD) was obtained using the WHO’s cut offs. A binary logistic regression model was used to analyze for associations between child-mother pair demographic variables and feeding indicators using SPSS 16.0. Of all the children, 60.0%, 57.0 % and 80.0 % did not meet MMF, MDD, and MAD respectively. Overall, 25.4%, 10.3% and 4.5% of children were stunted, underweight, and wasted respectively. The odds for meeting MMF were1.7 higher in children whose mothers had higher education. Children of older mothers had 2.0 more odds for MDD those born to teenage mothers. Children older than a year had more odds for MMF compared with those aged 6-11 months. The bulk of the children (80.0%) covered in the survey did not meet the WHO recommended infant feeding indicators. The District Health Management Team and other health professionals ought to intensify education aimed at improving child nutrition. Keywords:Complementary foods, Stunting, Wasting, Underweight, Anthropometry